A Literature Review: The Relationship of Family Resilience with The Incidence of Stunting in Children - Laili Rahayuwati; Alfiani Hidayanti; Arlette Suzy Puspa Pertiwi; Vira Amelia; Don Prisno; Myra D. Oruga (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2025)
Introduction: family  is  the  factor  that  influences  the  growth  of  children  in  a family.  Stunting  is  a  condition  that  must  be  of  special  concern  because  it  can resistor the physical development and mental of children. The family's role and function  in  increasing  family  resilience  is  very  needed  in  the  compliance nutritional status of children under five. Objectives: The aim of this study was to see  the  relationship  between  family  resilience  and  the  incidence  of  stunting  in children. Methods: This study used a literature review method, and the literature search  procedure  was  conducted  using  databases  such  as  PubMed  and  Google Scholar.  Keywords included "family resilience," "family role," "family function," "stunting,"  "malnutrition," and  "food  security." Inclusion criteria  covered  peer- reviewed  quantitative  studies  (cross-sectional,  case-control,  cohort)  published between 2016–2021 in English or Indonesian, with full-text availability. Exclusion criteria  included  non-full-text  articles,  narrative  reviews,  case  reports,  and unrelated topics. Results: Results 8 journals sorted by research topic. 2 journals discuss the role of family and family support on nutritional status related to stunting and 6  journals  discuss  food  security  related  to  stunting.  The  findings  indicate  that multiple  aspects  of  family  resilience,  including  family  roles,  food  security, parenting,  and  dietary  diversity,  play  a  crucial  role  in  preventing  stunting. Conclusions: From this study it was concluded that there was a relationship between family resilience with stunting in children.